2012
DOI: 10.1016/j.bbagen.2011.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The intracellular trafficking pathway of transferrin

Abstract: Background Transferrin (Tf) is an iron-binding protein that facilitates iron-uptake in cells. Iron-loaded Tf first binds to the Tf receptor (TfR) and enters the cell through clathrin-mediated endocytosis. Inside the cell, Tf is trafficked to early endosomes, delivers iron, and then is subsequently directed to recycling endosomes to be taken back to the cell surface. Scope of Review We aim to review the various methods and techniques that researchers have employed for elucidating the Tf trafficking pathway an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
326
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 354 publications
(378 citation statements)
references
References 114 publications
25
326
0
Order By: Relevance
“…Although to our knowledge, no study has assessed the global effect of attacking this endocytotic pathway during apoptosis, we can speculate that interfering with it is likely life-threatening to the cell because of the critical role it plays in absorbing external molecules. As examples, transferrin and lowdensity lipoprotein that are essential for iron and cholesterol uptake, respectively, rely on CCV for endocytosis of their cognate receptor [81,82]. Furthermore, as clathrin-mediated endocytosis is a crucial step in the signaling of many G protein-coupled receptors (GPCRs) [83] and receptor tyrosine kinases (RTKs) [84], halting this process is likely highly detrimental to the cell.…”
Section: Calm/picalmmentioning
confidence: 99%
“…Although to our knowledge, no study has assessed the global effect of attacking this endocytotic pathway during apoptosis, we can speculate that interfering with it is likely life-threatening to the cell because of the critical role it plays in absorbing external molecules. As examples, transferrin and lowdensity lipoprotein that are essential for iron and cholesterol uptake, respectively, rely on CCV for endocytosis of their cognate receptor [81,82]. Furthermore, as clathrin-mediated endocytosis is a crucial step in the signaling of many G protein-coupled receptors (GPCRs) [83] and receptor tyrosine kinases (RTKs) [84], halting this process is likely highly detrimental to the cell.…”
Section: Calm/picalmmentioning
confidence: 99%
“…Mutants Affecting the Cytoplasmic Side of hCTR1 Lack Copper-dependent Endocytosis-We used the elevated rate of copper uptake in cells expressing H139R to test a model for hCTR1-mediated copper transport in which it was proposed that hCTR1 contains extracellular binding sites for copper, which serve as a vehicle for copper transport after endocytosis of the hCTR1-copper complex (26,27), analogous to iron uptake by the transferrin receptor (32). The model is based on the observation that preincubation of cells in high copper conditions stimulates endocytosis of hCTR1 (26,27,31).…”
Section: Metal Ion Selectivity Of C-terminal Mutants-mentioning
confidence: 99%
“…77,78 In fact, Grimm et al 44 have demonstrated in primary fibroblasts and hepatocytes cultures from TPC2 KO mice that, in the absence of this channel, there is a damage in cholesterol trafficking and in the epidermal growth factor receptor (EGFR), that could be attributed to a dysfunction in endolysosomal degradation due to the absence of fusion between the lysosome and the endosome. 44 To note, mice deficient in TPC2 had liver damage, compatible with a non alcoholic esteohepatitis.…”
Section: Metabolismmentioning
confidence: 99%